First record of the genus Eleazara Distant (Hemiptera: Cicadellidae, Ledrinae) in Malaysia, with description of a new species - Huang, Weijian; Zhang, Yalin (Zootaxa, 2018)
The genus Eleazara Distant is reported from Malaysia for the first time based on one new species, E. viraktamathi sp. nov. This new species is described and illustrated. A checklist and key to the known species of Eleazara are provided.